Results Of Ranking Of Breeds From The World Collection Of The Silkworth From The World Collection Of Silkworth Research Institute Of Sericulture, Characterized By High Biological Indicators (Texas Journal of Agriculture and Biological Sciences, 2024)
Breeds from the world collection of silkworms research institute of sericulture, sex-marked at the green stage and characterized by high biological indicators, can be used to create 100% pure hybrids.